An asymmetric supercapacitor based on controllable WO3 nanorod bundle and alfalfa-derived porous carbon. Issue 59 (23rd November 2021) - Sun, Kanjun; Hua, Fengting; Cui, Shuzhen; Zhu, Yanrong; Peng, Hui; Ma, Guofu
Abstract : A asymmetric supercapacitor is assembled on the basis of an inerratic hexagonal-like WO3 nanorod bundle as a negative electrode and graphene-like alfalfa-derived porous activated carbon as the positive electrode in 1 M H2 SO4 aqueous electrolyte. Abstract : A novel asymmetric supercapacitor (ASC) is assembled on the basis of an inerratic hexagonal-like WO3 nanorod bundle as a negative electrode and graphene-like alfalfa-derived porous activated carbon (APAC) as the positive electrode in 1 M H2 SO4 aqueous electrolyte. The WO3 nanostructures prepared at pH of 1.6, 1.8, 2.0, 2.5 and 3.0 display hexagonal disc-like, nanorod bundle, inerratic hexagonal-like, sphere-like, and needle-shaped nanorod morphology. WO3 -2.0, which was prepared at a pH of 2.0, exhibits high specific capacitance (415.3 F g −1 at 0.5 A g −1 ). APAC-2, which had the mass ratios of dried alfalfa and ZnCl2 as 1 : 2, showed a 3D porous structure, large surface area (1576.3 m 2 g −1 ), high specific capacitance (262.1 F g −1 at 0.5 A g −1 ), good cycling stability with 96% of initial specific capacitance after 5000 consecutive cycles. The ASC assembled with WO3 -2.0 and APAC-2 exhibits high energy density (27.3 W h kg −1 at a power density of 403.1 W kg −1 ), as well as good electrochemical stability (82.6% capacitance retention after 5000 cycles). Such outstanding electrochemical behavior implies that the electrode materials are promising for practical energy-storage systems.